Safety of Tibolone as hormone replacement therapy in menopausal women: a scoping review (Revista Científica Integrada, 2024)
Objective: To evaluate the safety of tibolone as hormone replacement therapy in menopausal women. Methods: This is a scoping review conducted using the PubMed, Web of Science, and Scopus databases. Cohort studies, clinical trials, observational studies, and reviews were considered if they addressed the following guiding question: What evidence is available regarding the safety of tibolone as hormone replacement therapy in menopausal women? The selected studies had to be freely accessible in full text and published between 2014 and August 2024. The primary outcomes of interest included data on the safety of tibolone use, such as the risk of breast cancer, endometrial cancer, cardiovascular events, adverse effects, and impact on bone health. After cross-referencing controlled descriptors, 323 articles were found, of which 28 were selected. Results: Most of the articles were published in 2024 (21.43%), focusing on hormone therapy and the occurrence of cancer. Tibolone was found to be a relatively safe option, as it did not increase the risk of breast or ovarian cancer among menopausal and postmenopausal women. Conclusion: Tibolone demonstrates good efficacy and safety in hormone replacement therapy for menopausal and postmenopausal women, although its use should be carefully evaluated.
Keywords: Menopause; Middle Aged; Hormone Replacement Therapy; Patient Safety